USE OF PYCNOGENOL IN THE TREATMENT OF MELASMA: AN INTEGRATIVE REVIEW (REMUNOM, 2024)
Melasma is a pathology that directly affects melanocytes, and one of the main causes of this disease is photoaging of the skin. New medications are currently being developed for the treatment of melasma, however, there are still several developments regarding their uses regarding possible adverse effects. One of the methods used is pycnogenol. Thus, the objective of this study was to review the pharmacological potential of pycnogenol in the treatment of melasma. This article consists of an integrative review carried out through the collection of articles on the subject. Studies published from 2019 to 2024 were selected using health descriptors such as: melasma, treatments, pharmaceutical form, pycnogenol, therapy and medications. This article reviews the literature on the use of pycnogenol as a therapeutic alternative for the treatment of melasma, evaluating 9 studies selected by specific inclusion and exclusion criteria. The data indicate that pycnogenol, thanks to its antioxidant and anti-inflammatory properties, presents benefits in reducing hyperpigmentation, especially when used in combination with other treatments, such as lightening creams and sun protection. Pycnogenol appears to act on relevant mechanisms of action, including inhibition of tyrosinase and modulation of the inflammatory response, which help to contain the processes that aggravate melasma. Despite the promising results, there is a significant gap in controlled clinical studies evaluating the exclusive use of pycnogenol. The studies reviewed indicate benefits only in combination treatment contexts, which limits the understanding of its isolated efficacy. The need for more specific and well-designed research is highlighted, with the aim of validating pycnogenol as an independent and reliable option in the management of melasma.